2007
DOI: 10.1093/intqhc/mzm074
|View full text |Cite
|
Sign up to set email alerts
|

Testing the technology acceptance model for evaluating healthcare professionals' intention to use an adverse event reporting system

Abstract: The proposed model provides a means to understand what factors determine the behavioral intention of healthcare professionals to use an adverse event reporting system and how this may affect future use. In addition, understanding the factors contributing to behavioral intent may potentially be used in advance of system development to predict reporting systems acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
126
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 22 publications
15
126
2
Order By: Relevance
“…14 Wu et al found that subjective norms had the biggest effect on healthcare professionals' intention to use a report system of unwanted events. 21 Similarly, Hrisos et al demonstrated that subjective norms were an important factor in the prediction of physicians' intention to inspect diabetics' feet and to prescribe statine. 16 Finally, Khanna et al indicate that the subjective norms are one of the factors which explain physicians' intention to measure the body mass index of children and teenagers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Wu et al found that subjective norms had the biggest effect on healthcare professionals' intention to use a report system of unwanted events. 21 Similarly, Hrisos et al demonstrated that subjective norms were an important factor in the prediction of physicians' intention to inspect diabetics' feet and to prescribe statine. 16 Finally, Khanna et al indicate that the subjective norms are one of the factors which explain physicians' intention to measure the body mass index of children and teenagers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies carried out with healthcare professionals-often physicians-have indicated the importance of subjective norms in the prediction of intention. 14,16,[18][19][20][21] For example, Kortteisto et al indicate that subjective norms were a key factors in the prediction of healthcare professionals' intention to use clinical practice guidelines in their speciality field to make decisions concerning patients care. 20 Foy et al indicate that subjective norms contribute to predict healthcare professionals' intention to determine patients' knowledge, to use explicit terminologies and to investigate the meaning of diagnoses for patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the costs of a lack of acceptance of new systems has also been mentioned as one of the most significant reason for a need for managers to be careful about the way in which the deal with the acceptance of new technologies, as the possible economic ramifications of the failure of technological systems can be significant [23], [24]. The negative impact of the failure of systems can be significant, especially in the modern era as organizations are increasingly using information systems to gain and sustain a competitive advantage, and as the systems are becoming the integral part of the information systems in the organization [25], [26]. There issues are also important for managers, as they want to ensure that they are able to develop a deep understanding of the needs of their employees, and ensure that they put into practice those systems which motivate the employees, and can therefore improve the financial performance of the organization [27].…”
Section: Technology Acceptance Modelmentioning
confidence: 99%
“…For example, the indices of the above model are summarised as follows: (Hair et al, 2006;Joreskog & Sorbom, 1993). Furthermore, the value of 'Root Mean square Residual' (RMR) (0.004) in the above table is above the benchmark recommended by literature (≤ 0.05), (Hair et al, 2006;Wu et al, 2008;Wu et al, 2007;Hu & Bentler, 1995). The above table and the value of indices show that the final model depicted in Figure 2 has the ability to facilitate a KMS environment in the Indian business environment.…”
Section: The Proposed Theoretical Modelmentioning
confidence: 66%